Dilemmas Related to the Poland’s Participation in the Chinese Belt and Road Initiative - Tomaszewska, Paula; Pohl, Artur (Wydawnictwo Naukowe Wydziału Nauk Politycznych i Dziennikarstwa Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2019)
The aim of the article is to show the dilemmas related to the Poland’s participation in the Chi- nese Belt and Road Initiative. The theory behind the paper is that the Belt and Road Initiative has divided the mainstream of public discourse into two main threads: an optimistic option – one that sees opportunities in the participation in the initiative – and a pessimistic one, high- lighting the threats to the security of the Polish state. The authors will answer the following research questions: how is the BRI presented in the Polish public discourse? What are the main opportunities and challenges resulting from Poland’s accession to the initiative? A desk research analysis of all types of Polish-Chinese relations will also be conducted.

Celem artykułu jest ukazanie dylematów i postaw polskiego rządu związanych z uczestnictwem w chińskiej inicjatywie Belt and Road. Tezą pracy jest twierdzenie, że inicjatywa Belt and Road podzieliła główny nurt dyskursu publicznego na dwa główne wątki: opcję o optymistycznym nastawieniu – dostrzegającą szanse partycypacji w tej inicjatywie oraz dyskurs pesymistyczny – ukazujący zagrożenia dla bezpieczeństwa państwa polskiego. Autorzy odpowiedzą na nastę- pujące pytania badawcze: jak BRI jest przedstawiana w polskim dyskursie publicznym? Jakie są główne szanse i wyzwania wynikające z przystąpienia Polski do inicjatywy? Dokonana zostanie także analiza danych zastanych wszelkiego rodzaju płaszczyzn relacji polsko-chińskich.
Dylematy związane z uczestnictwem Polski w chińskiej inicjatywie Belt and Road
Keywords: the Belt and Road Initiative; BRI; China; Poland; the New Silk Road; Inicjatywa Pasa i Drogi; Chiny; Polska; Nowy Jedwabny Szlak